Importance of brucellosis vaccination in heifers aged 3 to 8 months (Research, Society and Development, 2025)
Bovine brucellosis is a zoonosis with significant sanitary, economic, and social impacts, requiring effective preventive measures for its control. This article presents a literature review on the importance of vaccination against brucellosis in heifers aged 3 to 8 months, addressing the consequences of lack of immunization on animal reproduction, livestock productivity, economy, and public health. Failure to vaccinate promotes the spread of Brucella abortus, leading to spontaneous abortions, stillbirths, infertility, and chronic bacterial transmission among herds. Furthermore, it results in trade restrictions and high costs for disease control, culling infected animals, and productivity losses. In the context of public health, brucellosis is a zoonotic disease that can be transmitted to humans, especially affecting rural workers and consumers of unpasteurized products. Finally, this study emphasizes that mandatory vaccination, combined with serological testing and biosecurity measures, is essential for disease eradication, ensuring livestock sustainability, and protecting food security for the population.